Effects of different combinations of organic fertilizers on the yield and quality of four leafy vegetables - Huabo Liu; Jianfeng Chen; Libo Fu; Hua Chen; Yanxian Yang; Wei Wang; Zhiyuan Wang; Ziqian Wan; Mei Yin (Scientific Reports)
Abstract This study investigates the effects of various combinations of organic fertilizers on the yield and quality of four common leafy vegetables: Chinese cabbage, asparagus lettuce, Shanghai green, and oilseed lettuce. The aim is to provide insights into how different organic fertilizer formulations can enhance vegetable production, improve nutrient content, and promote sustainable agricultural practices. Four fertilizer treatments were applied with equivalent NPK levels: (1) sheep manure-only (CK), (2) LCN (1:1 sheep manure-green manure), (3) MCN (2:1:1 sheep manure-green manure-straw), and (4) HCN (1:1 sheep manure-straw). The experiments were conducted in Kunming and Dali, Yunnan Province, China, over the 2020–2021 growing seasons. While no significant differences in yield were observed among treatments, notable species-specific variations in vegetable quality were found. The LCN treatment significantly increased vitamin C content in Chinese cabbage and asparagus lettuce, while green manure alone resulted in the highest chlorophyll content. The soluble sugar content showed significant differences among treatments within different species. Nitrate levels varied across species, with the MCN treatment reducing nitrate accumulation in Chinese cabbage and the HCN treatment reducing it in oilseed lettuce. Principal component analysis (PCA) indicated that LCN and MCN were the most effective treatments, with LCN optimizing quality for Chinese cabbage and asparagus lettuce, while MCN provided balanced nutrient benefits for Shanghai green and oilseed lettuce. These findings suggest that species-specific organic fertilization strategies, based on precise nutrient combinations, can optimize both productivity and nutritional quality in leafy vegetable farming.